Trends in Network and Communications International Conferences, NeCOM 2011, WeST 2011, and WiMON 2011, Chennai, India, July 15-17, 2011, Proceedings - Wyld, David C.; Wozniak, Michal; Chaki, Nabendu; Meghanathan, Natarajan; Nagamalai, Dhinaharan (Communications in Computer and Information Science,, 2011)
This book constitutes the proceedings of three International Conferences, NeCoM 2011, on Networks & Communications, WeST 2011, on Web and Semantic Technology, and WiMoN 2011, on Wireless and Mobile Networks, jointly held in Chennai, India, in July 2011. The 74 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers address all technical and practical aspects of networks and communications in wireless and mobile networks dealing with issues such as network protocols and wireless networks, data communication technologies, and network security; they present knowledge and results in theory, methodology and applications of the Web and semantic technologies; as well as current research on wireless and mobile communications, networks, protocols and on wireless and mobile security.